Cognitive and metacognitive beliefs: separating GAD from chronic worry - Styba-Nelson, Kevin (My University, 2025)
While chronic worry is a core component of generalized anxiety disorder (GAD), experiencing severe worry is not equivalent to having the disorder. The aim of the current analysis was to investigate if anxiety-related dysfunctional beliefs may help differentiate GAD from chronic worry. Participants included a community sample of adults (N = 624), collected from across Canada, and an undergraduate sample (N = 1020) collected from MacEwan University. A series of multiple linear regressions were conducted with both samples, with anxiety sensitivity, intolerance of uncertainty, and metacognitive beliefs about worry used as the predictor variables. The dependent variables were worry severity, GAD symptoms, and GAD symptoms when controlling for worry severity. Across both samples, worry severity was consistently predicted by social anxiety sensitivity, prospective and inhibitory intolerance of uncertainty, and both positive and negative metacognitive beliefs about worry. GAD symptoms were predicted across both samples by social anxiety sensitivity, prospective and inhibitory intolerance of uncertainty, and negative metacognitive beliefs about worry. However, only cognitive anxiety sensitivity and negative metacognitive beliefs that worry is dangerous or uncontrollable emerged as consistent predictors of GAD symptoms when controlling for worry severity. These two factors emerging as the only consistent predictors of GAD symptoms while controlling for worry severity could indicate that fears about one’s sanity and well-being, and beliefs that worry in uncontrollable, may be what leads chronic worry to progress to clinical GAD. These findings align with past research that has found significant success in treating GAD by targeting metacognitive beliefs. The current study supports the idea that chronic worry alone does not necessarily lead to GAD, and that fears regarding one’s mental health and worry are important components of the disorder.
Presented May 1-3, 2025, at the Canadian Association of Cognitive Behavioural Therapies' 15th Annual Conference held at the Banff Centre for Arts and Creativity in Banff, Alberta.
Keywords: generalized anxiety disorder (GAD); chronic worry; anxiety-related dysfunctional beliefs; metacognitive beliefs